2009
DOI: 10.1002/oti.274
|View full text |Cite
|
Sign up to set email alerts
|

Valuing difference: caregiving by mothers of children with disabilities

Abstract: Mothers who are caregivers of children with disabilities seek to have their children accepted and valued by others in society. This is supported by many reports of studies from different countries that involved mothers of children with disabilities, as well as through publications by disability advocates. In this paper, qualitative research data from interviews with seven mothers of children with disabilities were reanalysed using Bourdieu's theory of practice and van Manen's phenomenological methodology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 7 publications
2
20
0
2
Order By: Relevance
“…A satisfying time allocation between different occupations in everyday life, i.e. occupational balance, has been shown to be important for good health [34,35]. The findings of the present study could be interpreted as showing that these mothers do not have occupational balance, and confirms the result of a previous study [36], which showed that the significant care needs associated with having a child with special needs increases the risk for occupational imbalance.…”
Section: Health and Occupational Balancesupporting
confidence: 88%
“…A satisfying time allocation between different occupations in everyday life, i.e. occupational balance, has been shown to be important for good health [34,35]. The findings of the present study could be interpreted as showing that these mothers do not have occupational balance, and confirms the result of a previous study [36], which showed that the significant care needs associated with having a child with special needs increases the risk for occupational imbalance.…”
Section: Health and Occupational Balancesupporting
confidence: 88%
“…Ways of coping and mental burnout of Bedouin mothers compared to Bedouin fathers of children with ASD disabled children [18]. Quantitative cohort studies and quasi-experiments in Latin America found that the sensation of tiredness and high demand on the parents caused by taking care of the child with ASD did not change in the time of the follow-up.…”
Section: The Bedouin Communitymentioning
confidence: 99%
“…A recent meta-analysis suggested that parenting stress is higher in parents of children with autism spectrum disorders or DS than in parents of typically development children (Hayes & Watson, 2013). Other studies have shown that the stress levels of mothers of children with DS are higher than those of mothers of non-disabled children (Esdaile, 2009;Lenhard, Breitenbach, Ebert, Schindelhauer-Deutscher, & Henn, 2005). Quantitative cohort studies and quasi-experiments in Latin America found that the sensation of tiredness and high demand on the parents caused by taking care of the child with DS did not change in the time of the follow-up.…”
Section: Descriptive Study In a Colombian Populationmentioning
confidence: 99%